2016
DOI: 10.1063/1.4963830
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking of pulse shape-dependent learning rules with a quantum dot memristor

Abstract: We present the realization of four different learning rules with a quantum dot memristor by tuning the shape, the magnitude, the polarity and the timing of voltage pulses. The memristor displays a large maximum to minimum conductance ratio of about 57000 at zero bias voltage. The high and low conductances correspond to different amounts of electrons localized in quantum dots, which can be successively raised or lowered by the timing and shapes of incoming voltage pulses. Modifications of the pulse shapes allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Previous attempts showed that such synaptic interactions can be emulated in top‐down fabricated devices based on Ag nanoclusters or 2D materials . Also, modulation of synaptic activity was reported by pulse shape engineering or light stimulation . Here, Ag‐NW network shows that the stimulation of a synaptic pathway (S10, Supporting Information) results in synaptic weight changes not only in the directly stimulated synapse but also in other nonstimulated synaptic pathways (Figure c), thus mimicking heterosynaptic facilitation.…”
mentioning
confidence: 57%
“…Previous attempts showed that such synaptic interactions can be emulated in top‐down fabricated devices based on Ag nanoclusters or 2D materials . Also, modulation of synaptic activity was reported by pulse shape engineering or light stimulation . Here, Ag‐NW network shows that the stimulation of a synaptic pathway (S10, Supporting Information) results in synaptic weight changes not only in the directly stimulated synapse but also in other nonstimulated synaptic pathways (Figure c), thus mimicking heterosynaptic facilitation.…”
mentioning
confidence: 57%
“…Hartmann et al demonstrated this concept via a sitecontrolled QD memory, in which four types of learning rules (asymmetric Hebbian, asymmetric anti-Hebbian, symmetric Hebbian, and symmetric anti-Hebbian) were realized. 420 The device consisted of a channel, a lateral four-gate system, and site-controlled QDs above the channel. Figure 29f depicted the device structure and the circuit diagram, and V pr and V po pulses were employed to mimic the pre-and postsynaptic input signals, respectively.…”
Section: Qd-based Electronics For Synaptic Functionsmentioning
confidence: 99%
“…(g) The emulation of learning rules by the QD memristor achieved by voltage pulses with different shapes, amplitudes, and timing. Reproduced with permission from ref . Copyright 2016 AIP Publishing.…”
Section: Qd-based Electronics For Brain-inspired Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a compositional space of >10 6 formulations that can be further explored via a facile solution-based processing [25][26][27][28]. Moreover, the integration of low-dimensional structures [110][111][112], mixed formulations [113,114], nanocrystals [22,115] and quantum dots [116,117] further expands the already vast degrees of freedom or internal state variables in perovskite-based memristors. In addition, the electrochemical reactivity of the mobile ion species with the top and bottom electrodes proves to be crucial in the switching type and performance of perovskite-based memristors [118][119][120].…”
Section: Perovskite-based Memristorsmentioning
confidence: 99%